Government Expenditure and Infrastructural Development in Nigeria: An Empirical Analysis of its Economic Effects - Ibrahim, Victoria Hauwa; Ameji, Enemona Negedu; Taiga, Usio Uchechi (NIU Journal of Social Sciences, 2023)
This study examined the impact of government expenditure on infrastructure development in Nigeria for the period 1986-2022. The research was guided by three research questions and objectives. The Ordinary Least Squares (OLS) estimation technique was employed for testing the hypotheses of the study. The result of the OLS analysis showed that government expenditure has a positive impact on health, education, and transport infrastructure development in Nigeria. To improve on the gains of infrastructure development in the Nigerian economy, the study recommends that government should encourage the health sector by increasing its funding to equip the infrastructure pertaining to health matters, government should intensify efforts to strengthen its source of revenue for spending on education, and there must be a greater private sector participation, particularly in the air transport and seaport development, as well as effective coordination among the national, state and local levels, on capital investment of transport projects. Keywords: Government Expenditure, Health, Education, Transport, Infrastructure Development, Nigeria.